ISOLASI DAN IDENTIFIKASI KAPANG PADA KACANG TANAH (Arachis hypogaea L.) YANG DIJUAL DI BEBERAPA PASAR TRADISIONAL DI PROVINSI BALI - Kartana, I Made; Wisaniyasa, Ni Wayan; Duniaji, Agus Selamet (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 2 No 1 (2013): Jurnal ITEPA)
The aims of this study are to determine the contamination of fungi in peanuts, to find out what kinds of fungi that contaminated of peanuts, and to know the populations of each kind of fungi in peanuts are sold in some traditional markets in the province of Bali. This research used descriptive analysis where displaying the results of the study in the form of images and tables. The sampling was Quota Sampling method by taking samples at several largest traditional markets in the province of Bali. The number of samples required 36 samples of local varieties peanut and 36 samples of rabbit varieties peanut which taken from some of traditional markets in the province of Bali. Samples were isolated using a PDA (Potato Dextro Agar). The incubation period of 5 days (120 hours) at room temperature (29 ° C). The identification and the purification were done until get the pure result with PDA (Potato Dextro Agar). The result showed that rabbit varieties peanut 80.56% were contaminated by fungi, while, 19.44% of rabbit varieties peanut were not contaminated. Whereas, the result of local varieties peanut 66.67% were contaminated and 33.33% were not contaminated by fungi. Each of rabbit varieties peanut and local varieties peanut was contaminated by four kinds of fungi such as: Aspergillus Niger, Aspergillus flavus, Aspergillus parasiticus, Penicillium sp
Keywords: Rabbit and Local varieties peanuts, Contamination of Fungi